PENGARUH POTENSI KEBANGKRUTAN, STRATEGI MANAJEMEN LABA DAN RESIKO INVESTASI TERHADAP VOLUME PERDAGANGAN SAHAM PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yopie Chandra (Jurnal Riset Akuntansi Terpadu, 2019)
Market reactions as measured by Stock Trading Volume are often investigated due to the publication of financial statements (profit publications), dividend distribution announcements, announcement of dividend increases, announcement of changes in directors, or Indonesian macro conditions which theoretically have the possibility of influencing the volume of stock trading. The market reaction is measured by the Stock Trading Volume starting from one day after the information is announced until the next few days, even until the next few months. The purpose of this study is to determine the extent of the effect of bankruptcy potential, profit management strategy and investment risk simultaneously on the stock trading volume of companies listed on the Indonesia Stock Exchange.This study uses quantitative methods. The population to be studied in writing scientific papers are all LQ45 Index companies listed on the Indonesia Stock Exchange. The sample in this study were all LQ-45 stock indices that persisted in the 2009-2011 period. The results of multiple linear regression analysis show that partially the variable (H1) potential for bankruptcy has a significant effect on the volume of stock trading. Variable (H2) The earnings management strategy partially does not have a significant effect on the volume of stock trading. Variable (H3) Investment risk partially has a significant effect on stock trading volume. Simultaneously (H4) the potential for bankruptcy, earnings management strategies and investment risk have a significant effect on the volume of stock trading.